Convenience dynamics and white-collar crime - Gottschalk, Petter (Routledge, 2021)
"This book introduces a dynamic perspective to study white-collar crime. It argues that as personal motives change over time, so too do organizational opportunities, and willingness for deviant behaviour. The work contends that the extent of white-collar crime is dependent on the extent of crime convenience perceived and preferred by potential offenders. It discusses how potential white-collar offenders expand organizational opportunities for financial crime over time. The dynamics are illustrated here by system dynamics models to capture cause and effect relationships. The book also presents a new structural model illustrating the elements of convenience theory along with a new dynamic model illustrating the evolution of white-collar crime. The practical aspects are illustrated with a number of case studies"--